0100 Perceptual Failure: An Under-recognised Source Of Error. (1st November 2014) - Greig, Paul; Higham, Helen; Nobre, Anna
Abstract : Background: Situational awareness is a 'safety-critical' skill in medicine, 1 but attentional focus narrows as individuals concentrate on tasks. Missing an event that would otherwise appear obvious is termed a perceptual error. Individuals greatly overestimate their perceptual reliability. 2 These forms of perceptual failure are well recognised in psychological literature, but little attention has been paid to them in medicine. This video-based experiment was designed to explore the hypothesis that perceptual errors affect clinicians. Methods: A bespoke video was created using the simulation centre of the OxSTaR Centre, University of Oxford, which incorporated a number of events designed to probe change- and inattentional-blindness. This sequence was based around a simulated adult resuscitation, and the events varied in clinical significance, from the irrelevant (a change in team members' clothing) to the highly relevant (disconnection of the patient's oxygen supply). Participants were stratified by resuscitation experience and professional background. Results: A clear advantage was seen in favour of the most experienced, who were more likely to notice clinically relevant events (change in CPR provider, appearance of a stethoscope, change in patient airway, disconnection of oxygen supply) although not the irrelevant change in hat colour. The observed trends surprisingly did not reach significance in the case of the oxygen disconnection, although they were significant in the other cases. For all events, even in the expert group, participants were still more likely to miss the event than to see it. Conclusions: These data suggest that clinicians are vulnerable to perceptual errors and that, although training confers an advantage, even experts are likely to miss important events when placed in taxing situations. Events such as oxygen malfunction would meaningfully affect patient outcome. Acquisition of accurate data is fundamental to good-quality situational awareness. These results imply perceptual error is a contributor to adverse events in practice. References: Vincent C. Patient Safety. 2nd ed. Oxford: Blackwell; 2010 Levin DT, Momen N, Drivdahl S. Change blindness blindness: the metacognitive error of overestimating change-detection ability. Vis cogn 2000;7(3):397–412